Pertanggung Jawaban Perdata Seorang Dokter dalam Kasus Malpraktek Medis (Lex Jurnalica, 2011)
Actually, this malpractice is not only related to the physician / health kalangangan, because other professions also can do as lawyers, teachers, journalists and others. However, because other professions less problematic than with health circles, the term is more attached to the health, especially among doctors. This will be discussed in this study is about How to implement the values contained in the Code of Medical Ethics Indonesia (Keki) for a doctor? How is accountability and medical personnel (doctors) in the event of a medical malpractice case? The objectives of the research conducted by the authors is to find out how to implement the values contained in the Code of Medical Ethics Indonesia (KEKI) for a doctor. and to find out how the accountability of medical personnel (doctors) in the event of a medical malpractice case. The method of writing this thesis is the normative method. Normative legal writing is also called the writing of literature (Library Research) is the research done by searching or reviewing and analyzing library materials or the materials ready-made documents.Keywords: Responsibility, Docter, Malpractice